2020
DOI: 10.1111/ene.14658
|View full text |Cite
|
Sign up to set email alerts
|

Added value of cerebrospinal fluid multimarker analysis in diagnosis and progression of dementia

Abstract: Background and purpose: Recently, some emerging cerebrospinal fluid (CSF) markers have been proposed as diagnostic tools for Alzheimer disease (AD) that can have an effect on disease progression. We analyze the accuracy of these CSF markers for diagnosis of AD in reference to brain amyloid positron emission tomography (PET). We also investigated whether they help in differentiating AD from other dementias and examined their influence in tracing the progression to dementia. Methods: Amyloid‐β (Aβ) 1–42, total t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Poorer visuospatial performance may be associated to pathology in the parietal lobe in early AD 53 . A relatively new biomarker strongly associated to cognitive performance in AD but also to differentiate AD from other underlying pathologies is the Ng/BACE ratio 54 . It has been shown that higher values of the Ng/BACE are associated with poorer memory performance in predementia AD patients 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Poorer visuospatial performance may be associated to pathology in the parietal lobe in early AD 53 . A relatively new biomarker strongly associated to cognitive performance in AD but also to differentiate AD from other underlying pathologies is the Ng/BACE ratio 54 . It has been shown that higher values of the Ng/BACE are associated with poorer memory performance in predementia AD patients 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers are not stand-alone tools and should always be interpreted along with clinical, neuropsychological, and imaging data. Keeping this in mind, analysis of classical CSF biomarkers, especially when incorporated in a classification/diagnostic system such as the AT(N), may offer a significant diagnostic tool [90,91], with both added [92] and prognostic [36] value, allowing the correct identification of AD during life, especially in cases with atypical or mixed presentations [93]. This is always important for correct therapeutic decisions, and it is of paramount importance currently, due to the recent approval of aducanumab as a disease-modifying treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping the above limitations in mind, biomarkers are not useful only in research, but also in clinical practice, showing both added and prognostic value [78,79]. They are not only able to confirm the presence of AD in typical cases, but they are able to identify AD in cases with atypical presentations such as primary progressive aphasia, corticobasal syndrome and posterior cortical atrophy [34,35,80,81].…”
Section: Discussionmentioning
confidence: 99%